Characteristic Features and Construction Technique of Shipwreck Yenikapı 20 - Işıl Özsait Kocabaş; Taner Güler (Art-Sanat)
During the salvage excavations carried out in the Yenikapı district of Istanbul between 2004 and 2013 within the scope of the Marmaray and Metro projects, the Theodosius Harbor, the essential commercial transportation center of Constantinople, was unearthed. Yenikapı 20 (YK20) is one of 37 shipwrecks discovered in Theodosius Harbor. YK20 is dated to AD 687-975 years by radiocarbon analyses. The preserved dimensions of the shipwreck, whose hull part is intact, are 8.76 m in length and 2.25 m in width. After in situ documentation, the hull was removed from the site; post-excavation documentation and construction technique studies were carried out at Istanbul University Yenikapı Shipwrecks Application and Research Center. According to archaeological evidence and preliminary reconstruction studies, YK20 is a small merchantman with a length of approximately 10.76 m, with Latin sails, built using the Mediterranean mixed construction method. It has similar construction characteristics to the Yenikapı shipwrecks YK9, YK12, and YK18, which have chestnut planks and planking edge dowel joints. In this article, the Yenikapı excavations, which lasted for nine years, and the history of the harbor are presented to create integrity with the subject, the documentation of the shipwreck is summarized, its general construction features and analysis are evaluated in comparison with the other Yenikapı shipwrecks.